Donkey Milk: An Overview of its Chemical Composition and Main Nutritional Properties or Human Health Benefit Properties - Živkov Baloš, Milica; Ljubojević Pelić, Dragana; Jakšić, Sandra; Lazić, Sava (Journal of equine veterinary science, 2023)
•A review of nutritional and health benefit properties of donkey milk has been performed.•Fat, cholesterol and protein contents are low in donkey milk.•Minerals and vitamins contents are high in donkey milk.•It is rich in lysozyme, essential fatty acids and shows strong antioxidant activity.•New updated clinical trials based on use of donkey milk in human nutrition are necessary. The donkey milk has a remarkable similarity to human milk, in addition to its valuable nutritional composition and content of numerous immune factors. The donkey milk is the subject of research worldwide, and data from the literature suggest significant differences with respect to the contents of individual components. However, some basic characteristics of donkey milk have been established: low contents of fat and cholesterol, total proteins and casein and high contents of lactose, whey proteins, calcium, selenium, and Vitamin D3. The donkey milk is rich in various protective proteins (α-lactalbumin, lysozyme, lactoferrin, lactoperoxidase, and immunoglobulins), and shows strong antioxidant, antibacterial, antiviral, antifungal, hypoglycemic, antiparasitic, and antitumor activity. Donkey milk can be considered functional food, having in mind that its fatty-acid profile and content of essential fatty acids are beneficial for cardiac health. The total fat content in donkey milk is low compared to human milk, and for this reason it is necessary to enrich donkey milk with other fat in order to provide enough calories in a diet for children. Commercialization of donkey milk and dairy products is still limited due to low production levels, that is lack of products on the market, and lack of product information. Considering the research data from the literature, there is a need for human clinical trials in order to obtain a stronger evidence of the therapeutic properties of donkey milk.